Contemporary Perspectives on Primary Education - O'Doherty, Teresa (Education Matters, 2022)
Education has changed dramatically because of Covid-19. We are learning to live and work with levels of precariousness that we never thought possible. How prepared are our children and our system for this fast-changing world? This overview of primary education looks at the key themes in the sector and how the landscape is set to continue changing in the coming years.
Keywords: Education; Covid-19; teacher education programmes; Curriculum Reform; Inclusion; teacher supply